2021
DOI: 10.3390/molecules26216490
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Harmirins, Novel Harmine–Coumarin Hybrids as Potential Anticancer Agents

Abstract: As cancer remains one of the major health burdens worldwide, novel agents, due to the development of resistance, are needed. In this work, we designed and synthesized harmirins, which are hybrid compounds comprising harmine and coumarin scaffolds, evaluated their antiproliferative activity, and conducted cell localization and cell cycle analysis experiments. Harmirins were prepared from the corresponding alkynes and azides under mild reaction conditions using Cu(I) catalyzed azide–alkyne cycloaddition, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…Thus, compound 28 possibly targeted both nuclear DNA and cytoplasmic targets ( Figure 2 ). This was contrary to our previous finding that harmine derivatives did not enter the cell nuclei [ 34 ]. A longer incubation period did not improve the fluorescence signal, while the 5-fold higher concentration disrupted the cell morphology (data not shown).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, compound 28 possibly targeted both nuclear DNA and cytoplasmic targets ( Figure 2 ). This was contrary to our previous finding that harmine derivatives did not enter the cell nuclei [ 34 ]. A longer incubation period did not improve the fluorescence signal, while the 5-fold higher concentration disrupted the cell morphology (data not shown).…”
Section: Resultscontrasting
confidence: 99%
“…Numerous studies have shown that harmine significantly influences the cell cycle of various cancer cell lines, including HCT116, via induction of G2/M cell cycle arrest, intercalation into DNA and induction of DNA fragmentation; upregulation of p53 and p21 expression; and downregulation of cyclin B1, p-cdc2, cdc2, cdc25, and p-cdc25 expression necessary for G2/M transition [ 47 , 48 , 49 ]. In our previous paper, we also confirmed that the parent compound harmine induced arrest in the G1 phase of MCF-7 cells already after 24 h, along with a reduction in cells in the S phase and an additional accumulation of cells in the G2/M phase after 48 h. The O-7-substituted TT harmine–coumarin derivative, which was synthesized by our research group, caused even more prominent G1 arrest than harmine, accompanied by a drastic reduction in the percentage of cells in the S phase, which also persisted after 48 h [ 34 ]. Harmicene 28 , also an O-7-substituted TT-harmine derivative, had an even more pronounced effect on the HCT116 cell cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoplasm is the only location for the unique harmine and coumarin hybrid known as Harmirin. Moreover, harmirin generated a significant G1 arrest and decreased the proportion of cells in the S phase, indicating that it may impede DNA synthesis rather than DNA damage to exert its antiproliferative action [89] …”
Section: β‐Carbolines’ Anticancer Activity Through Modulation Of Hall...mentioning
confidence: 99%
“…[ 97 ] Coumarin‐1,2,3‐triazole‐harmine hybrids 138 (IC 50 : 1.9–13.3 µM, MTT assay) demonstrated considerable antiproliferative activity against MCF‐7 breast cancer cells, and the most active hybrids 138a,b (IC 50 : 2.2 and 1.9 µM) were more potent than 5‐fluorouracil (IC 50 : 23.9 µM) and harmine (IC 50 : 13.5 µM). [ 177 ] 1,2,3‐Triazole tethered coumarin‐pyrimidinone/β‐lactam hybrids only showed weak to moderate antiproliferative activity against MCF‐7 breast cancer cells, revealing that pyrimidinone and β‐lactam were not suitable pharmacophores to combine with coumarin through 1,2,3‐triazole. [ 178,179 ]…”
Section: 23‐triazole Acted As a Linkermentioning
confidence: 99%